Translation of Healing Labor: Japanese Sex Work in the Gendered Economy – from the perspective of George Steiner's hermeneutic translation theory - Wu, Jiatong (Nanyang Technological University, 2023)
This capstone project has translated an excerpt from the third chapter from the book Healing Labor: Japanese Sex Work in the Gendered Economy written by Gabriele Koch and published in 2020. The excerpt introduces how Japanese female sex workers deal with the stigma of working in an illicit industry contradictory to normative notions of feminine respectability. The original texts narrate from an ethnographic perspective and apply a plain and analytical writing style. Challenges and difficulties in the translation process consist of conveying cultural terms paraphrased from Japanese into English, certain multivalent expressions and contextual implications in a target-culture-oriented way. With reference to George Steiner’s Hermeneutic Translation Theory, the translator discusses the comprehension and delivery processes in this capstone at length, following the four moves in translation, namely, initiative trust, aggression, incorporation and compensation. A key outcome of this project is a faithful Chinese version corresponding to the original texts both linguistically and culturally with translation strategies including but not limited to back translation, domestication, paraphrase, omission and annotation. This project will serve as a useful reference for future translation practices concerning multicultural issues.